2019
DOI: 10.1111/dom.13879
|View full text |Cite
|
Sign up to set email alerts
|

Favourable effect of the sodium‐glucose co‐transporter‐2 inhibitor canagliflozin plus the dipeptidyl peptidase‐4 inhibitor teneligliptin in combination on glycaemic fluctuation: An open‐label, prospective, randomized, parallel‐group comparison trial (the CALMER study)

Abstract: This multicentre, prospective, randomized, open‐label, blinded‐endpoint, parallel‐group, short‐term (4–5 weeks) controlled trial was conducted to investigate the superiority of the effect of reducing mean amplitude of glycaemic excursions (MAGE) during meal tolerance tests (MTTs) for the combination of dipeptidyl peptidase‐4 (DPP‐4) inhibitor and sodium‐glucose co‐transporter‐2 (SGLT2) inhibitor compared with SGLT2 inhibitor monotherapy. Ninety‐nine patients with type 2 diabetes who were taking teneligliptin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…Also, our data from the linear mixed-effects model showed a rapid BG drop during hemodialysis and a tendency for hypoglycemia in the subsequent nighttime period in maintenance hemodialysis patients with type 2 diabetes. Although DPP-4 inhibitors have been shown to improve BG variability in patients with type 2 diabetes in many randomized controlled trials (RCTs) [41][42][43][44][45][46][47][48][49] (see the table in the Electronic supplementary material), few studies have reported the same effect in maintenance hemodialysis patients [50]. Our study illustrates the usefulness of DPP-4 inhibitors in these patients.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Also, our data from the linear mixed-effects model showed a rapid BG drop during hemodialysis and a tendency for hypoglycemia in the subsequent nighttime period in maintenance hemodialysis patients with type 2 diabetes. Although DPP-4 inhibitors have been shown to improve BG variability in patients with type 2 diabetes in many randomized controlled trials (RCTs) [41][42][43][44][45][46][47][48][49] (see the table in the Electronic supplementary material), few studies have reported the same effect in maintenance hemodialysis patients [50]. Our study illustrates the usefulness of DPP-4 inhibitors in these patients.…”
Section: Discussionmentioning
confidence: 55%
“…The ability of DPP-4 inhibitors to suppress BG variability in patients with type 2 diabetes has been shown in studies using CGM [51, 52]. Furthermore, several RCTs using CGM found that BG variability is suppressed more effectively by DPP-4 inhibitors than by other agents such as sulfonylureas [41,42] and sodium glucose cotransporter 2 inhibitors [43][44][45] [41,49], or had used metformin only [41][42][43]46]. There have also been some reports on the usefulness of DPP-4 inhibitors in patients on hemodialysis [50], but none has shown obvious suppression of BG variability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DPP-4 inhibitors have been shown to decrease BG levels in T2DM patients by continuous glucose monitoring (CGM) [ 48 , 49 , 50 ]. In addition, various randomized controlled trials have shown by CGM that DPP-4 inhibitors suppress BG levels more efficiently than other agents such as sulfonylureas [ 51 , 52 ] or sodium glucose cotransporter 2 inhibitors [ 53 , 54 , 55 ] when used in combination with insulin administration [ 56 , 57 ]. DPP-4 inhibitors that enhance insulin secretion and decrease prandial glucagon levels have been shown to improve BG levels [ 49 ], and reductions in prandial glucagon levels are considered to underlie improvements in BG levels by DPP-4 inhibitors [ 58 ].…”
Section: Dpp-4 Inhibitors Improve Blood Glucose Responsementioning
confidence: 99%
“…In the present study, we carried out secondary analyses of the sodium‐glucose co‐transporter‐2 inhibitor canagliflozin plus the dipeptidyl peptidase‐4 inhibitor teneligliptin in combination on glycaemic fluctuation: An open‐label, prospective, randomized, parallel‐group comparison trial (CALMER study) 5 to investigate the effect of combination therapy with dipeptidyl peptidase‐4 (DPP‐4) inhibitor and sodium–glucose cotransporter 2 (SGLT2) inhibitor in comparison with switching from DPP‐4 inhibitor to SGLT2 inhibitor on improving the GV in patients with or without impaired endogenous insulin secretion.…”
Section: Introductionmentioning
confidence: 99%